1989
DOI: 10.1055/s-2008-1071295
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographical and Morphological Examination of Subependymal Cystic Lesions in Maturely Born Infants

Abstract: The clinical data and development of 8 cases with subependymal cysts detected on neurosonography in the neonatal period were studied, and the prognosis was found to vary. Also, clinico-pathological examination of 15 autopsied cases of congenital subependymal cysts (SEC) was performed, with immunohistochemical staining involving neuron-specific enolase in three cases, which revealed that congenital SEC are often complicated by various degrees of brain and heart anomalies, and suggested that SEC might occur in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 7 publications
5
28
0
4
Order By: Relevance
“…Subependymal cysts and subependymal germinolysis have been described in the clinical literature; however, the demise of the cells in the germinal matrix has been generally attributed to rubella virus, cytomegalovirus, radiation or anti-mitotic drugs [25]. The demonstration that hypoxia/ischemia in the immature rat without hemorrhage or infection dramatically and chronically depletes the SVZ is a novel finding.…”
Section: Discussionmentioning
confidence: 84%
“…Subependymal cysts and subependymal germinolysis have been described in the clinical literature; however, the demise of the cells in the germinal matrix has been generally attributed to rubella virus, cytomegalovirus, radiation or anti-mitotic drugs [25]. The demonstration that hypoxia/ischemia in the immature rat without hemorrhage or infection dramatically and chronically depletes the SVZ is a novel finding.…”
Section: Discussionmentioning
confidence: 84%
“…SEP were reported in 0.5–5% of healthy term infants,2 20 21 in 3–5.23% of preterm infants2124 and in 4.1% of all admissions to a neonatal unit 25. SEP are associated with congenital infections, especially cytomegalovirus and rubella,21 23 24 2628 with many metabolic disorders, for example Zellweger syndrome, mitochondrial disorders and sulphite oxidase deficiency,29 congenital abnormalities such as cardiac defects21 30 and a host of genetic abnormalities. A recent meta-analysis showed that there is a 20–25% chance of an underlying chromosomal anomaly or congenital infection if bilateral SEP are found on cUS;31 however, that review included asymptomatic and symptomatic term and preterm infants and not just term infants considered clinically normal as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Subependymal cysts seem to have a good prognosis if isolated [3,5], but the exclusion of other pathologies should be exhaustive, including neuronal migration disorders and other extracranial anomalies [7,8], apart from the ones referred before. Nevertheless, prenatal parental counseling is not simple even in isolated subependymal cysts.…”
Section: Discussionmentioning
confidence: 99%